Constituent Structure of the Simple Sentences Found in Peter Pan Novel - Ernawati, Ni Wayan Sri; Maharani , Putu Devi; Putra , I G B Wahyu Nugraha (Journal of Language and Applied Linguistics, 2024)
The study aims to analyse the constituent structure of the simple sentences which were constructed in the “Peter Pan” novel. This research used descriptive qualitative method. The steps in taking and collecting the data were reading the novel, underlining the simple sentences, and analysis the constituent structures. The theory of Brown and Miller (1991) to represented the tree diagram and constituent structures. And used the theory of Quirk et al (1973) to support the analysis. Based on the results, this research found that there were 182 data of simple sentences which were used in the “Peter Pan” novel by J. M. Barrie. The sentences which were found divided into two branches, those are Noun Phrase (NP) and Verb Phrase (VP). Most of the Noun Phrase (NP) that was found in the sentences have the daughter of Determiner, Noun and Pronoun. Meanwhile, the Verb Phrase have the daughters, there were Auxiliary, Verb, Noun Phrase, Prepositional Phrase, Adjective Phrase and Adverbial Phrase.